Den danske salme i Amerika - Mortensen, Enok (Grundtvig-studier, 1974)
The Danish Hymn in America By Enok Mortensen This essay, the author of which has worked for the greater part of his life in the U.S.A. as a pastor in Danish churches, presents the background of the history of Grundtvig’s hymns in America up to the present day. First he emphasizes the importance of the fact that Danish emigrants nearly always took a hymn book with them, and that when he visited the sick and the old, they would be able to produce this, in most instances Roskilde Konvents Salmebog from 1855, the first to include Grundtvig’s hymns. Then a brief account is given of the hymn books published by the Danish immigrants themselves, since the establishment in 1872 of a Kirkelig Missionsforening (Evangelical Union) with the periodical Kirkelig Samler. It is true that in 1867 Louis Jørgen Hauge the Baptist had already published a hymn book entitled Psalmer og aandelige Sange and had himself translated or written a quarter of the 422 hymns. In 1910 the Mormons also produced a collection of Danish hymns and songs, entitled Sion Sange, including hymns by Grundtvig rewritten to the memory of Joseph Smith, the prophet, and his brother Hyrum. These non-Lutheran communities soon joined their American counterparts. The majority of Danish immigrants, however, preserved the connection with the Danish national church, used the services authorized in Denmark and the above-mentioned Danish hymn book, which was issued in several impressions by a publishing house in Blair, Nebraska.Among the new hymn books published in America the writer mentions especially the Dansk Folkesamfunds Sangbog, edited by Grundtvig’s son, the clergyman F. L. Grundtvig, which went through several impressions (the most recent in 1931) and which is still used. The publisher was convinced that Danish immigrants would make the best Americans by remaining Danish. Danish was also their language at home; but in the second and third generations English was adopted and people began to experiment with church services in English and with English translations of Danish hymns.The first rendering in English of a Danish hymn is Ingemann’s Igennem Nat og Trængsel (Through the night of doubt and sorrow), which had already been translated in 1867 by the hymnist Sabine Baring-Gould; it is also found in many American hymn books and is frequently sung. But the first translation of a Grundtvig hymn is that by Mary Elizabeth Fellowes of Tag det sorte Kors fra Graven (From the grave that dark cross take), of which the first and last verses are quoted. She also translated Vær velkommen, Herrens Aar (Welcome God’s year). None of her translations, however, have been included in any hymn book.The prosody is imperfect but her understanding of the content of the hymns is amazing. Not until 1927 did a Danish hymn book appear in English: Hymnal for Church and Home, which was last printed in 1954 and contained 454 hymns, of which 131 were translations from the Danish. These included 9 by Ingemann, 17 by Kingo, 37 by Brorson and 52 by Grundtvig, among them being Montgomery’s Du som gaar ud fra den levende Gud, retranslated into English.Among the translators special mention is made of the Danish-American pastors P. G. Poulsen, J. C. Aaberg and S. D. Rodholm together with the Norwego-American pastor Carl Doving. Many extracts from their translations are quoted and the translations themselves criticized. It seems, for instance, that Rodholm’s skill as a translator increased with the years; many of his hymns have been as deeply loved as the originals. Finally follow three translations of and comments on three Grundtvig polms by Dr. Johannes Knudsen who, like Dr. Enok Mortensen, the author, is a member of a committee appointed by the Danish Interest Conference of the Lutheran Church in America to cooperate with the Grundtvig Society on a three-volume edition in English of selections from Grundtvig’s works.When the Lutheran Churches in America united in 1960 and 1962, it was feared in Danish circles that the tone of the Danish hymns would be swamped by the multitude of American hymns. This fear was justified. The big common hymn book for Lutherans which was published in 1958 contained only 17 Danish hymns (out of a total of 602), including 1 by Brorson, 2 by Ingemann, 4 by Kingo and 7 by Grundtvig. None of Rodholm’s translations was among these. In the Danish Church (which was still functioning in 1958) an attempt was made to overcome this deficiency through a supplement, which is still used in many communities of Danish background. The translations were revised by a committee, thus giving expression to the justifiable criticism of new generations.